Critical behavior of the three-dimensional ±J Ising model at the paramagnetic-ferromagnetic transition line - Hasenbusch, Martin; Toldin, Francesco Parisen; Pelissetto, Andrea; Vicari, Ettore (Physical review. B, Condensed matter and materials physics, 2007)
We study the critical behavior of the three-dimensional ±J Ising model [with random-exchange probability P(Jxy)=pδ(Jxy−J)+(1−p)δ(Jxy+J)] at the transition line between the paramagnetic and ferromagnetic phases, which extends from p=1 to a magnetic-glassy multicritical point at p=pN≈0.768. By a finite-size scaling analysis of Monte Carlo simulations at various values of p in the region pN<p<1, we provide strong numerical evidence that the critical behavior along the ferromagnetic transition line belongs to the same universality class as the three-dimensional randomly dilute Ising model. We obtain the results ν=0.682(3) and η=0.036(2) for the critical exponents, which are consistent with the estimates ν=0.683(2) and η=0.036(1) at the transition of randomly dilute Ising models.
Im Titel ist "+" hochgestellt und "-" tiefgestellt
Gesehen am 09.09.2022